Optimization of machining process parameters in Al 7175 metal matrix composites using Taguchi method. (2021) - Chenneswari, P.; Sateesh, N.; Ram Subbiah,; Pavan, C.
Abstract: Aluminum-based metal matrix composites (MMC) have been used in various applications in the aerospace and automotive industries. Accomplishing a uniform circulation of support inside the framework is one such challenge, which influences straightforwardly on the properties and nature of composites. MMC is one of the authentic sources to satisfy the demand for engineering materials such as hardness, toughness, high tensile strength, low density, and good wear resistance. In this research work, Al 7175 metal matrix composites reinforced with 25% weight fraction of Sic and 4% weight fraction of graphite were synthesized through stir casting. Experiments were carried out based on L9 standard orthogonal array design for turning operation on Al 7175 using a tungsten carbide tool with three input process parameters, namely cutting speed, feed and depth of cut. The effect of input parameters on performance characteristics such as the material removal rate (MRR) and surface roughness (Ra) was studied. The signal to noise ratio was used to study the performance characteristics in turning operation. Results revealed that Ra reduced either on increasing spindle speed or by reducing feed, but depth of cut was not influential on Ra. MRR increased with increasing any of the three input parameters.